A study of the complications among the patients undergoing retroperitoneal and transperitoneal laparoscopic nephrectomy for pyonephrosis - Patil, Milind; Baria, Manish; Parmar, Ankita (International Journal of Research in Medical Sciences, 2019)
Background: Nowadays laparoscopy have gained wider acceptance in urology that leads to more reports on the potential complications. This study was conducted to evaluate the complications among the patients undergoing retroperitoneal and transperitoneal laparoscopic nephrectomy. Methods: Analysis was done retrospectively through review of a maintained database of 219 consecutive laparoscopic simple nephrectomies done for pyonephrosis from July 2001 to February 2013 at the department of urology Civil Hospital and B J Medical College Ahmedabad. Results: Total 219 simple nephrectomies performed between July 2001 to February 2013 for pyonephrosis. In 165 (75.3%) of patient’s procedure was through trans peritoneal route while retroperitoneal access was used in 54(24.6%) patients. In our study there were major complications in 12 patients with laparoscopic transperitoneal group and in 4 patients in laparoscopic retro peritoneal group. The minor complication rate in present study was 13.3% (22/165) in laparoscopic transperitoneal group and 11.1% (6/54) in laparoscopic retroperitoneal group. Conclusions: There were major complications in patients with laparoscopic transperitoneal group and in few patients in laparoscopic retro peritoneal group. In most other series it was seen that retroperitoneoscopic surgery may be associated with more complications, the findings are unfounded. Minor complications can be managed easily if there is low threshold for conversion to open surgery.